Epidemiological, clinical, and molecular studies on nail disorders in the human population of Punjab, Pakistan - Muhammad Tariq Shafi; Ali Umar; Muhammad Wajid (Molecular Biology Reports, 2026)

Insights on inflammatory pathways and their cross-talk: a comprehensive review on asthma - Sadaf Naz; Aimen Wajid; Marya Nawaz Malik; Muhammad Khalid Tipu (Molecular Biology Reports, 2026)

Epitranscriptomic regulation of plant–pathogen interactions and disease resistance - Muhammad Tahir Naseem; Wajid Zaman (Physiological and Molecular Plant Pathology, 2026)

Mechanistic reprogramming by stem cell-derived extracellular vesicles: From cargo sorting to tissue regeneration - Muhammad Faizan Khan; Hina Wajid; Sumreen Begum (Tissue and Cell, 2026)

Portable metagenomics for preventive surveillance and outbreak control in livestock and poultry: Pathogen detection, resistome profiling, and antimicrobial stewardship - Muhammad Saeed Akhtar; Wajid Zaman (Research in Veterinary Science, 2026)

From biosynthesis to food market translation of pullulan: AI-assisted production, structure-property-function interplay, regulatory perspectives, and commercialization - Muhammad Wajid Ullah; Su Sun; Zainab Jamil; Omar Mohammad Atta; Lili Zhang; Maleeha Azhar; Hidayat Ullah; Faryal Taimour; Mazhar Ul-Islam; Sehrish Manan; Yimin Fan; Zhiguo Wang (Carbohydrate Polymers, 2026)

Contamination levels, eco-health risks, and source identification of some potentially toxic elements in roadside dust along the Indus Highway (N-55), Pakistan using compositional data analysis - Amanullah; Wajid Ali; Saad Khan; Said Muhammad; Abdur Raziq; Muhamamd Nafees; Imran Ud Din (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Pollutant triggers at ocean interfaces: how microhabitats rewire microbial biodegradation and valorization - Mati Ullah; Muhammad Arif; Wajid Hussain; Tariq Ahmad (Marine Chemistry, 2026)

Reversible -NH2/-NH3+ switching drives proton-coupled electron transfer for selective CO2-to-CO photoreduction in S-scheme MOF/g-C3N4 heterojunction - Sharafat Ali; Sher Ali; Ahmed Ismail; Yong Wang; Syed Ul Hasnain Bakhtiar; Qaisar Alam; Pir Muhammad Ismail; Wajid Ali; Ahmad Iqbal; Polycarpos Falaras; Jiabao Yi; Fazal Raziq; et al. (Chemical Engineering Journal, 2026)

Selenium and Vitamin E restore redox balance, gut microbiota and reproductive function against cadmium-induced toxicity in male rabbits - Ayesha Gill; Mudasser Habib; Amjad Hameed; Wajid Ishaque; Muhammad Kashif Saleemi; Rida Fatima; Ali Dogan OMUR; Tarique Hussain (Journal of Hazardous Materials, 2026)

Coordination-assisted deconstruction of cellulose supramolecular structure enables room-temperature dissolution and high-performance regenerated materials - Enqing Zhu; Lili Zhang; Hangyu Shen; Sihuan Wang; Jiao Meng; Leixin Huang; Zhengjun Shi; Muhammad Wajid Ullah; Jinyuan Cheng; Jinxia Ma; Yimin Fan; Zhiguo Wang (Chemical Engineering Journal, 2026)

Environmental pharmaceutical and antibiotic mixtures: An exposomics-guided framework for mechanistic toxicology - Muhammad Saeed Akhtar; Wajid Zaman (Toxicology Letters, 2026)

Toxicology and biodistribution of plant-derived extracellular vesicles for drug delivery: Quality control, safety mechanisms, and translational testing priorities - Muhammad Tahir Naseem; Wajid Zaman (Toxicology Letters, 2026)

Nanotechnology driven paradigms for sustainable agriculture: A holistic assessment of efficacy, mechanisms, and environmental footprint - Wajid Saeed; Samavia Mubeen; Sana Basharat; Qiqi Peng; Aliya Ayaz; Enerand Mackon; Muhammad Umer; Furkhanda Kalsoom; Muhammad Waseem; Yun li; Pingwu Liu (European Journal of Agronomy, 2026)

Geochemical Characterization of Saidgai and Katora Lakes for Irrigation, Drinking, and Health Risk Indices, Hindu Kush Region - Said Muhammad; Tufail Ahmad; Wajid Ali; Adnan Ali Khan; Cem Tokatli; Ashfaq Ahmad; Zafar Iqbal (Water, Air, & Soil Pollution, 2026)

Phosphoric Acid Outperforms Diammonium Phosphate (DAP) in Cadmium Toxicity Alleviation by Decreasing Bioavailability and Optimizing Maize Physiology in Contaminated Alkaline Soil - Nadeem Sarwar; Mujahid; Muhammad Akhtar; Imtiaz Ahmed; Wajid Mahboob; Muhammad Imran Tipu; Muhammad Rashid Shaheen; Mashael Daghash Alqahtani; Usman Zulfiqar (Water, Air, & Soil Pollution, 2026)

Nanoencapsulated EO-based drug delivery for pest control: from chemistry to formulation design - Wajid Zaman; Asma Ayaz; Muhammad Zafar; Adnan Amin (Protoplasma, 2026)

Sustainable cellulose beads for continuous-flow photocatalytic water purification with rapid mineralization and long-term stability - Lili Zhang; Xi Guan; Chun Shi; Muhammad Wajid Ullah; Zhiguo Wang; JinXia Ma (Journal of Environmental Chemical Engineering, 2026)

Sequential bacterial-fungal fermentation upgrades Juncus effusus into an antibacterial biosorbent for cationic dyes - Hai-Juan Zhao; Su Sun; Zhen-Yu Wang; Li Chen; Muhammad Wajid Ullah; Yan-Bo Zhang; Jian-Gang Zhou (Biomass and Bioenergy, 2026)

Soil-mediated Rhizobacteria Modulate SA-JA Transcriptional Antagonism in Tomato to Enhance Systemic Resistance Against a Specialist and a Generalist Herbivore - Muhammad Wajid Javed; Jam Nazeer Ahmad; Samina Tanwir; Ahmad Nawaz (Journal of Soil Science and Plant Nutrition, 2026)
Salicylic (SA) and jasmonic acid (JA) defense pathways antagonize each other to compromise host plant defense. Modulation of SA-JA transcriptional antagonism could enhance plant resistance against herbivores. Tomato, Solanum lycopersicum , was treated with phytohormonal inducers BTH (Benzothiadiazole-SA synthetic analogue) and MeJA (Methyl jasmonate-JA analogue) through foliar applications at 0, 0.5, and 1 mM, while PGP rhizobacteria ( Bacillus sp. Mb01 and Pseudomonas sp. Mb05) were applied through roots using a randomized block design having three replications. RNA transcripts of SA responsive genes ( PR1a and PAL ) and JA eliciting genes ( PIN2 and LOX ) were studied. Individual application of SA/JA synthetic analogues improved the levels of their respective marker genes but generated an antagonism by masking each other’s expression. Conversely, individual and combined treatment with rhizobacteria modulates SA/JA antagonism to enhance the expression of SA marker genes under MeJA treatment and of JA marker genes under BTH treatment. This improvement was tested against a specialist (whitefly, Bemisia tabaci ) and a generalist herbivore (tomato fruit borer, Helicoverpa armigera ) to assess enhanced pest resistance. Although SA and MeJA reduced the mean larval weight, larval survival, and adult emergence of H. armigera along with the mean nymph population of B. tabaci , the results were more pronounced when inducers were applied along with rhizobacteria. Instead of separate applications of BTH/MeJA, their combined application with PGPR is recommended to improve hostplant resistance against phytophagous pests. However, investigations on other SA and JA eliciting genes, PGPR species, and pests are required to implement these findings in a broader crop -pest spectrum.

Biopolymer Coated Urea Improves Wheat Productivity and Nitrogen Use Efficiency by Optimizing Plant Physiology and Mineral Acquisition - Wisha Khan; Muhammad Akhtar; Abdul Rasool Awan; Wajid Mahboob; Nadeem Sarwar (Journal of Soil Science and Plant Nutrition, 2026)

Pharmaco-therapeutic modulation of the Glo1–Nrf2–RAGE functional network in chronic inflammation: polyphenols in the context of current anti-inflammatory therapy - Sajid Ali; Muhammad Saeed Akhtar; Adnan Amin; Atif Ali Khan Khalil; Wajid Zaman (Inflammopharmacology, 2026)

Cobalt nanostructures induced hematotoxicity and renal toxicity in albino mice: an experimental and computational evaluation - Ali Umar; Muhammad Saleem Khan; Muhammad Wajid (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Assessment of Coagulansin-A’s therapeutic potential and safety in an ovalbumin (OVA) induced airway inflammation model - Sadaf Naz; Muhammad Usama Mazhar; Aimen Wajid; Rimsha Noor; Lin Zhu; Muhammad Khalid Tipu (Inflammopharmacology, 2026)

A comprehensive review of the phytochemical, and pharmacological potential of Alnus hirsuta (Spach) Rupr., (Siberian Alder): implications for anti-inflammatory therapeutics - Sajid Ali; Adnan Amin; Muhammad Saeed Akhtar; Khizar Abdullah Khan; Ishaq N. Khan; Imran Khan; Wajid Zaman; Atif Ali Khan Khalil (Inflammopharmacology, 2026)

Mineral chemistry and alteration characteristics of sulfide-bearing metavolcanics in the Thalle area, Kohistan–Ladakh Arc: insights into magmatic-hydrothermal fluid evolution - Muhammad Farhan; Tehseen Zafar; Mohammad Arif; Chun-Feng Li; Zahid Hussain; Zaheen Ullah; Syed Wajid Hanif Bukhari; Uzair Siddique; Syed Ali Turab; Mubasir Ali (Geosciences Journal, 2026)

Advances in Understanding Cold Tolerance Mechanisms in Potato (Solanum Tuberosum L.): Physiological, Biochemical, Molecular, and Breeding Perspectives - Barkat Ali; Wajid Anwar; Muhammad Nauman Khan (American Journal of Potato Research, 2026)

Soil amendments enhance phenolic defense in canola, suppressing cabbage aphid population and improving yield performance - Muhammad Wajid Javed; Mansoor–ul Hasan; Muhammad Sagheer; Shahbaz Talib Sahi (International Journal of Tropical Insect Science, 2026)

Bio-Elicitors Could Perform Better Over Synthetic Insecticides in Promoting Plant Growth, Nutrient Acquisition, and Aphid Resistance in Canola Through Phenolic Enhancement - Muhammad Wajid Javed; Muhammad Sagheer (Journal of Soil Science and Plant Nutrition, 2026)

Simultaneous quantification of hydroxycinnamate derivatives and antioxidant activity of Ziziphus oxyphylla Edgew. leaf methanolic extract - Surriya Naheed; Muhammad Wajid; Afsheen Ehsan; Khalid Hussain; Gulzar Muhammad; Naureen Shehzadi; Muhammad Tanveer Khan; Imran Ahmad; Adnan Ashraf (Natural Product Research, 2026)

Genome-wide identification, functions, and expression analysis of carbonic anhydrase gene family in the gills of O. niloticus under salinity stress - Ahmad Waheed; Samra Farooq; Jabbir Ali Khan; Imran Ahmad Khan; Samra Shafqat; Hina Naz; Muhammad Saleem Khan; Muhammad Wajid (Aquaculture, 2026)

Water Quality deterministic and Probabilistic Health Risks Assessment using Monte Carlo Simulation: Case Study from a Semi-Arid Region - Said Muhammad; Zeeshan Raza; Wajid Ali; Ashfaq Ahmad; Cem Tokatli; Imran Ud Din (Water, Air, & Soil Pollution, 2026)

Exploring the Links Between Variations in Snow Cover Area and Climatic Variables Across the Upper Indus Basin Under a Changing Climate - Hafsa Muzammal; Muhammad Zaman; Jaehak Jeong; Kashif Mehmood; Syed Aftab Wajid (International Journal of Climatology, 2026)
The Upper Indus Basin (UIB) has experienced gradual changes in water supply due to variations in the Snow Cover Area (SCA) in recent decades. This study examined daily snow cover changes using satellite imagery from the Moderate Resolution Imaging Spectroradiometer (MODIS) Aqua (2002–2022) and Terra (2001–2022) via Google Earth Engine. An Auto‐regressive Integrated Moving Average (ARIMA) model was developed using time series data to predict SCA. Model accuracy was assessed using Stationarity, ACF, and PACF plots, as well as performance metrics, including AIC, BIC, RMSE, and MSE. The most appropriate iteration (0,1,1) (3,1,1) of the best‐performing model showed strong agreement between observed and simulated SCA, with R 2 values of 0.72 for calibration (2017–2020) and 0.84 for validation (2021–2023). Predicted SCA was further correlated with climate change variables (precipitation, maximum and minimum temperature) from NASA Earth Exchange (NEX) Global Daily Downscaled Projections under SSP1‐2.6 and SSP5‐8.5 scenarios. Results showed a significant decline in SCA, with moderate negative correlations ( r = −0.82 to −0.72) under SSP1‐2.6 and stronger correlations ( r = −0.99 to −0.81) under SSP5‐8.5. Precipitation showed a non‐significant correlation with SCA ( r = 0.14 ± 0.41under SSP1‐2.6; r = 0.11 ± 0.52 under SSP5‐8.5) with decreasing snow cover %. Regionally, Astore, Zanskar, Shigar, and Shingo exhibited significant SCA reductions (tau = −0.585 ± −0.002; p = 0.036 ± p ≤ 0.0001). The Indus_Downstream subbasin showed a non‐significant decreasing trend (tau = −0.002; p = 0.961). These findings highlight the challenges in maintaining runoff, hydropower generation, and freshwater storage, particularly in high‐altitude regions, due to uncertainties in SCA predictions under climate scenarios.

Mechanistic insights into the enhancement of azithromycin biodegradation by extracellular polymeric substances: Roles of metabolic activity, electron transfer, and reactive oxygen species - Jian-Gang Zhou; Ming-Hong Wei; Shi-Jie Wang; Li Chen; Muhammad Wajid Ullah; Hong-Tao Liu; Su Sun (Journal of Hazardous Materials, 2026)

Geochemical modeling, evaluation of contaminants and impacts of land use, land cover patterns on groundwater quality in Khushab, Pakistan - Hasnain Abbas; Javed Iqbal; Syed Madhi Haider Kazmi; Maqsood Ahmed; Muhammad Ismail; Wajid Hussain (Journal of Contaminant Hydrology, 2026)

Ultrahigh solid loading biorefinery with deep eutectic solvent pretreatment for lignin fractionation and nanoparticle preparation - Enqing Zhu; Jinyuan Cheng; Leixin Huang; Hangyu Shen; Jiao Meng; Shaoning Wang; Zhengjun Shi; Muhammad Wajid Ullah; Jinxia Ma; Lili Zhang; Zhiguo Wang (Chemical Engineering Journal, 2026)

Moringa oleifera: a comprehensive review with special emphasis on phytochemistry - Muhammad Nazim; Wajid Raza; Faiz ul Hassan Nasim; Shazia Anjum; Hammad Ullah; Asif Nawaz; Muhammad Ayaz; Maria Daglia (Phytochemistry Reviews, 2026)

Natural products in medicinal chemistry: targeting inflammatory pathways with plant-derived compounds - Adnan Amin; Muhammad Saeed Akhtar; Atif Ali Khan Khalil; Sajid Ali; Wajid Zaman (Medicinal Chemistry Research, 2026)

In-silico genome-wide identification of ADF gene family in Brassica napus under long-term high-temperature stress - Enerand Mackon; Shanshan Zhang; Zhuyu Pan; Muhammad Ikram; Latif Ullah Khan; Wajid Saeed; Muhammad Waseem; Yun Li; Pingwu Liu (Genetic Resources and Crop Evolution, 2026)

Emerging strategies in engineering nanomaterials for overcoming cancer stem cell-mediated therapy resistance - Chaofan Huang; Xianhui Ning; TianZhi Liu; Xiaohong Li; Muhammad Wajid Ullah; Kang Yang; Yonggang Lv (Chemical Engineering Journal, 2025)

Bacterial polysaccharides in the food industry: Synthesis-structure-properties relationships, AI-driven innovations, regulatory challenges, and bioeconomy prospects - Muhammad Wajid Ullah; Sehrish Manan; Khulood Fahad Alabbosh; Mazhar Ul-Islam; Omar Mohammad Atta; Asif Ali Khan; Yimin Fan; Khalid Ali Khan; Noureddine Elboughdiri; Zhiguo Wang (Carbohydrate Polymers, 2025)

Hybrid ensembled machine learning algorithm for landslide susceptibility assessment and data enhancement via Dual Discriminator Conditional Generative Adversarial Network - Sajid Hussain; Bin Pan; Wajid Hussain; Meer Muhammad Sajjad; Muhammad Ali; Zeeshan Afzal; Rebouh Nazih Yacer; Aqil Tariq (Natural Hazards, 2025)

Phytoremediation potential of native tree species for lead removal under domestic wastewater irrigation: a nature-based solution for urban water pollution - Amina Kanwal; Muhammad Farhan; Mehmooda Munazir; Hossam S. El-Beltagi; Qaiser Farid Khan; Qamar uz Zaman; Huma Qureshi; Tauseef Anwar; Wajid Zaman; Dilbar Bazarbayeva; Khairiah Mubarak Alwutayd; Muneera A. Saleh; et al. (Environmental Monitoring and Assessment, 2025)

Heavy metals contamination of roadside dust, risk assessment, and their spatial distribution along the M-1 motorway - Sehrish Amin; Wajid Ali; Said Muhammad; Saeeda Yousaf; Ashfaq Ahmad; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Water quality, risk assessment indices, and source apportionment across spatial patterns - Said Muhammad; Nizam Ullah; Wajid Ali; Sehrish Amin; Cem Tokatli; Imran Ud Din; Zafar Iqbal; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

The nexus between global value chains and productivity gains of ASEAN countries - Zia Ur Rahman; Wajid Khan; Musarat Abbas; Fatima Gulzar; Muhammad Azhar Farooq (Environment, Development and Sustainability, 2025)

Lignin-regulated MOF@lignocellulose aerogels for enhanced selective carbon dioxide adsorption - Jiaqing Zhang; Bin Wu; Shaoning Wang; Enqing Zhu; Muhammad Wajid Ullah; Khalid Ali Khan; Lili Zhang; Zhiguo Wang (Carbohydrate Polymers, 2025)

The generative adversarial neural network with multi-layers stack ensemble hybrid model for landslide prediction in case of training sample imbalance - Wajid Hussain; Hong Shu; Hasnain Abbas; Sajid Hussain; Isma Kulsoom; Saqib Hussain; Hajra Mustafa; Aftab Ahmed Khan; Muhammad Ismail; Javed Iqbal (Stochastic Environmental Research and Risk Assessment, 2025)

Comparative Analysis of the Efficiencies of Two Low Cost Adsorbents for Carbon Dioxide Capture - Sayyaf Yousaf; Haris Abdullah Noor; Muhammad Wajid Ullah; Alireza Noorpoor; Adnan Ahmad Tahir; Maria Siddique; Romana Khan (International Journal of Environmental Research, 2025)

Integration of multivariate indices to correlate pollen morphology and evolutionary adaptations in halophytes - Moona Nazish; Asif Kamal; Muhammad Azhar Khan; Khursheed Ur Rahman; Mohamed Soliman Elshikh; Sarah Abdul Razak; Fozia Bibi; Jawaher Alkahtani; Wajid Zaman (Genetic Resources and Crop Evolution, 2025)

Assessing alkaline battery waste toxicity in Nile tilapia (Oreochromis niloticus): integrating physiological biomarker analysis with molecular docking insights - Ahmad Waheed; Habiba Zafar; Hina Naz; Jabbir Ali Khan; Samra Shafqat; Muhammad Saleem Khan; Muhammad Wajid (Ecotoxicology, 2025)

Sulphur Nutrition Improves Plant Growth Performance Against a Specialist Herbivore by Eliciting Phenolic Defense and Nutrient Induction in Rapeseed - Muhammad Wajid Javed; Dilbar Hussain; Muhammad Hasnain; Mubshar Hussain; Imran Ali (Journal of Plant Growth Regulation, 2025)

Integrated PSInSAR and SBAS-InSAR analysis for landslide detection and monitoring - Sajid Hussain; Bin Pan; Wajid Hussain; Meer Muhammad Sajjad; Muhammad Ali; Zeeshan Afzal; M. Abdullah-Al-Wadud; Aqil Tariq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Spatial distribution, potential health risks, and sources of groundwater contamination in the semi-arid region - Owais Rabbani; Wajid Ali; Ghazanfar A. Khattak; Said Muhammad; Muhammad Nafees; Shahid Iqbal; Imran Ud Din; Ashfaq Ahmad; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Balancing Nitrogen Application to Enhance Soil Health and Mitigate Heavy Metal Contamination Risks in Sweet Potato Cultivation - Rafiq Ahmad; Cheng-cheng Si; Shah Fahad; Wajid Ali Khattak; Muhammad Zakir (Journal of Soil Science and Plant Nutrition, 2025)

Toxicological risk assessment and sources of heavy metal(loid)s using compositional data analysis, Astore River Basin, Himalaya - Wajid Ali; Said Muhammad; Cem Tokatli; Ashfaq Ahmad; Zhang Luyuan (Marine Pollution Bulletin, 2025)

A critical review of opportunities and challenges of solid waste management in an emerging economy- evidence from Pakistan - Sajid Rashid; Hameeda Sultan; Wajid Rashid; Bushra Danish Talpur; Roberto Xavier Supe Tulcan; Muhammad Tariq Khan; Eve Bohnett; Muhammad Safar Korai; Lixiao Zhang (Environmental Development, 2025)

Spatial distribution of hazard index via heavy metals consumption in water from the himalayan lacustrine ecosystems - Said Muhammad; Tauseef Ahmed; Sehrish Amin; Cem Tokatli; Fikret Ustaoğlu; Ashfaq Ahmad; Wajid Ali; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Epidemiology and genetic characterization of Alternaria alternata causing leaf spot in Fragaria × ananassa - Nasir Mehmood; Abid Riaz; Salman Ghuffar; Sadaf Anwaar; Nyla Jabeen; Isha Shaheen; Muhammad Qasim; Salma Saeed Khan; Muhammad Rauf; Tauseef Anwar; Huma Qureshi; Ghadah Salim Abusalim; et al. (Fungal Biology, 2025)

Silicon-mediated Nutrient Deterrence Could Reduce Aphid (Brevicoryne brassicae L.) Abundance and Improve Crop Yield by Eliciting Phenolic Defense in Canola (Brassica napus L.) - Muhammad Wajid Javed; Mansoor-ul -Hasan; Muhammad Sagheer; Shahbaz Talib Sahi (Journal of Soil Science and Plant Nutrition, 2025)

Synergistic Application of Biochar and Bio-Organic Phosphate Enhances Drought Tolerance in Maize by Modulating Antioxidant Defense and Reducing Oxidative Stress - Ghulam Sarwar; Zainab Zahra; Tauseef Anwar; Huma Qureshi; Faizan Khalid; Muhammad Waqar Hassan; Muhammad Younus; Muhammad Sajid-ur-Rehman; Huma Rao; Faisal Shahzad; Wajid Zaman; Mansour Shrahili; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Pollen patterns and morphological variability unraveling taxonomic relevance and evolutionary relationship in salt-tolerant species - Moona Nazish; Asif Kamal; Muhammad Zafar; Mushtaq Ahmad; Ghulam Mujtaba Shah; Jawaher Alkahtani; Khursheed Ur Rahman; Mohamed Soliman Elshikh; Sarah Abdul Razak; Muhammad Tahir Naseem; Wajid Zaman (Genetic Resources and Crop Evolution, 2025)

Induced resistance and nutrient deterrence reduce aphid reproduction and improve crop yield, phenolic defense, and economic benefits of canola (Brassica napus L.) in the field - Muhammad Wajid Javed; Mansoor-Ul-Hasan; Muhammad Sagheer; Shahbaz Talib Sahi (Arthropod-Plant Interactions, 2025)

Morpho-physiological attributes, antioxidant activities, proximate seed analysis, and phytoremediative prospective of two castor bean genotypes in lead spiked soil - Sahar Naveed; Sajid Mahmood; Wajid Ishaque; Muhammad Akhtar (Acta Physiologiae Plantarum, 2025)

Role of plant growth-promoting rhizobacteria in sustainable agriculture: Addressing environmental and biological challenges - Abdul Wahab; Farwa Batool; Gholamreza Abdi; Murad Muhammad; Shahid Ullah; Wajid Zaman (Journal of Plant Physiology, 2025)

Retraction Note: Evaluation of toxicity potential of cobalt in wheat irrigated with wastewater: health risk implications for public - Fu Chen; Zafar Iqbal Khan; Asma Zafar; Jing Ma; Muhammad Nadeem; Kafeel Ahmad; Shehzadi Mahpara; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; et al. (Environmental Science and Pollution Research, 2025)

Assessing the Influence of Potassium Fertilizer Variations on Growth, Yield, and Crop Quality of Sugarcane (Saccharum officinarum L.) Genotypes - Wajid Ali Hisbani; Bonface O. Manono; Muhammad Nawaz; Kashf Mehmood; Zuhair Hasnain; Afroz Rais; Sohail Irshad; Danish Ibrar; Manzer H. Siddiqui; Saud Alamri; Shahbaz Khan (International Journal of Plant Production, 2025)

Recent advances in engineering non-native microorganisms for poly(3-hydroxybutyrate) production - Said Nawab; Muhammad Wajid Ullah; Syed Bilal Shah; Ya-Fei Zhang; Hareef Ahmed Keerio; Yang-Chun Yong (World Journal of Microbiology and Biotechnology, 2025)

The role of agricultural land management in modulating water-carbon interplay within dryland ecological systems - Wajid Ali Khattak; Jianfan Sun; Fawad Zaman; Abdul Jalal; Muhammad Shafiq; Sehrish Manan; Rashida Hameed; Ihtisham Khan; Irfan Ullah Khan; Khalid Ali Khan; Daolin Du (Agriculture, Ecosystems & Environment, 2025)

Sustainable production of flocculant-containing fungal mycelium composite for removal of non-steroidal anti-inflammatory drugs - Jiangang Zhou; Kai Xu; Xintong Hu; Yajun Cai; Muhammad Wajid Ullah; Yanbo Zhang; Su Sun (Journal of Cleaner Production, 2025)

Mitigation of salinity stress in sunflower plants (Helianthus annuus L.) through topical application of salicylic acid and silver nanoparticles - Muhammad Shahbaz; Tauseef Anwar; Sammer Fatima; Nilgün Onursal; Huma Qureshi; Waseem Akhtar Qureshi; Naimat Ullah; Walid Soufan; Wajid Zaman (Physiology and Molecular Biology of Plants, 2025)

The pivotal role of arbuscular mycorrhizal fungi in enhancing plant biomass and nutrient availability under drought stress conditions: A global meta-analysis - Fawad Zaman; Muhammad Umair Hassan; Wajid Ali Khattak; Ahmad Ali; Mohamed F. Awad; Fu-Sheng Chen (Science of The Total Environment, 2024)

Potentially harmful elements contamination, risk assessment, and their bioaccumulation in food crops - Imran Ud Din; Said Muhammad; Cem Tokatli; Inayat ur Rehman; Wajid Ali; Mohammed Rafi Shaik; Mohamed E. Assal; Ayaz Ul Haq; Shaik Althaf Hussain (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Fabrication and characterization of bioactive curdlan and sodium alginate films for enhancing the shelf life of Volvariella volvacea - Asif Ali Khan; Feng-Jie Cui; Muhammad Wajid Ullah; Abdul Qayum; Ibrahim Khalifa; Syed Asim Shah Bacha; Zheng-Zi Ying; Ismail Khan; Umar Zeb; Abdullah A. Alarfaj; Mohammad Javed Ansari; Yan Yang; et al. (Food Bioscience, 2024)

Structure-property relationship of ultrasound-assisted nanoemulsion-impregnated bioactive polysaccharide films for enhanced shelf life of mushrooms - Asif Ali Khan; Muhammad Wajid Ullah; Abdul Qayum; Ibrahim Khalifa; Mazhar Ul-Islam; Syed Asim Shah Bacha; Umar Zeb; Fang-Jie Yao; Sulaiman Ali Alharbi; Mansour Shrahili; Yan Yang; Wei Jia; et al. (Food Packaging and Shelf Life, 2024)

Association of polymorphism of NLRP3, ICAM-1, PTPN22, INS genes in childhood onset type 1 diabetes in a Pakistani population - Anjum Jabeen; Samreen Riaz; Muhammad Usman; Asia Parveen; Maryam Mukhtar; Abdul Wajid; Atif Hanif; Andleeb Batool (Molecular Biology Reports, 2024)

Nutritional composition assessment and antimicrobial activity of Catostylus perezi , jellyfish blooms along the coast of Pakistan: an awareness to avoid food neophobia in Pakistan - Muhammad Naveed; Malik Wajid Hussain Chan; Sadar Aslam; Fenghuan Wang; Anas Sajjad; Asad Ullah; Nida Saleem; Muhammad Samee Haider; Victoria Arija (Natural Product Research, 2024)

Construction of visible-light-driven 2D/2D NiFe2O4/g-C3N4 Z-scheme heterojunction photocatalyst for effective degradation of organic pollutants and CO2 reduction - Wisal Muhammad; Wajid Ali; Muhammad Asif Khan; Fawad Ali; Amir Zada; Muhammad Zaka Ansar; Pow-Seng Yap (Journal of Environmental Chemical Engineering, 2024)

Microplastic pollution in aquatic ecosystem: A review of existing policies and regulations - Muhammad Tariq Khan; Sajid Rashid; Unzile Yaman; Saeed Ahsan Khalid; Asif Kamal; Mushtaq Ahmad; Nasrin Akther; Md Abul Kashem; Md Faysal Hossain; Wajid Rashid (Chemosphere, 2024)

CRISPR/Cas-mediated genome editing for efficient tomato breeding: past achievements and future directions - Muhammad Naeem; Wajid Zaman; Saddam Saqib; Asim Shahzad; Saeed ur Rahman; Naveed Ahmad (South African Journal of Botany, 2024)

Ecofriendly Approach for the Determination of Selected Aldehydes by Fluorescence Quenching of L-Tryptophan - Muhammad Naeem Khan; Syeda Qandeel Wajid Kazmi (Journal of Fluorescence, 2024)

Nanoparticle-Mediated Mucosal Vaccination: Harnessing Nucleic Acids for Immune Enhancement - Wajid Hussain; Sadia Chaman; Hafiza Nazia Koser; Syed Muhammad Aun; Zainab Bibi; Ayesha Nasir Pirzadi; Jawad Hussain; Zubaria Zubaria; Ghulam Nabi; Muhammad Wajid Ullah; Shenqi Wang; Ishrat Perveen (Current Microbiology, 2024)

Non-linear ground deformation detection and monitoring using time series InSAR along the coastal urban areas of Pakistan - Sajid Hussain; Bin Pan; Zeeshan Afzal; Wajid Hussain; Yin Jianhui; Meer Muhammad Sajjad; Muhammad Ali (Environmental Science and Pollution Research, 2024)

Comparative analysis of physicochemical properties and biological activities of crude polysaccharides isolated from selected Auricularia cornea strains - Asif Ali Khan; Fang-Jie Yao; Feng-Jie Cui; Yu Li; Lixin Lu; Ismail Khan; Abdul Jalal; Ming Fang; Khulood Fahad Alabbosh; Mohamed F. Awad; Noureddine Elboughdiri; Muhammad Wajid Ullah (Food Bioscience, 2024)

Characterization of Exopolysaccharides Having Potential Antiviral Properties from Priestia Aryabattai Strain MK1 and Bacillus sp. Strain MK2 - Maham Khan; Muhammad Imran; Muhammad Ashraf; Wajid Ishaque; Mudasser Habib (Current Microbiology, 2024)

Optimizing Micronutrient Supplementation in Mango Orchards for the Suppression of Mango Anthracnose (Colletotrichum gloeosporioides) - Wajid Nazir; Syed Atif Hasan Naqvi; Niaz Ahmed; Ateeq ur Rehman; Abdulwahed Fahad Alrefaei; Muhammad Asif Zulfiqar; Ummad ud Din Umar (Applied Fruit Science, 2024)

A multiplex PCR assay to detect mislabelling in fish products - Komal; Shahid Sherzada; Muhammad Imran; Saeed Akram Khan; Abdul Wajid (Food Additives & Contaminants Part B-Surveillance, 2024)

Exploring the variability of root system architecture under drought stress in heat-tolerant spring-wheat lines - Asadullah; Shahmir Ali Kalhoro; Wajid Farhad; Azhar Iqbal; Sultan; Abdul Waheed; Muhammad Rashid; Syed Rehmat Ullah Shah (Plant and Soil, 2024)
Background and aims Global wheat production is under threat due to climate change, specifically heat and drought and their combination. This study aims to address the root trait responses of heat-tolerant wheat genotypes to drought. Methods The variability in root traits of CIMMYT wheat lines, which were previously developed for heat stress tolerance (HTWL), was evaluated alongside 10 Pakistani-approved varieties under three cultivation conditions and soil moisture levels. Results Our findings revealed that the plasticity of the wheat root system is highly pronounced, with rhizosphere conditions exerting a more substantial influence (5–49%) than the genotypic response (1–14%). Furthermore, in the hydroponic and pot system, we noted higher maximum-root length (1.5–1.8 fold) and root-to-shoot ratio (3.4–10.6 fold) as compared to field condition, while the root biomass was substantially higher in the field trial (3-57 fold). Nonetheless, persistent drought conditions exerted contrasting impact with reduction in most of the traits except specific root length and harvest index which were increased under drought. Conclusions The variation in root traits against drought indicates the potential for the development of improved genotypes that can withstand multiple stresses. Furthermore, it is crucial to consider rhizosphere conditions when selecting genotypes, as the plasticity of wheat roots may lead to misinterpretations if rhizosphere conditions are disregarded. Root dry weight and root-to-shoot ratio are more stable traits as compared to maximum root length and specific root length. It is recommended to evaluate a broader range of rhizosphere conditions to select tolerant genotypes.

Characterizations of biogenic selenium nanoparticles and their anti-biofilm potential against Streptococcus mutans ATCC 25175 - Binbin Si; Yang Yang; Muhammad Naveed; Fenghuan Wang; Malik Wajid Hussain Chan (Journal of Trace Elements in Medicine and Biology, 2024)

Extremophiles and their enzymatic diversity and biotechnological potential - Fatima Atif; Nida Maqsood; Wajeeha Ali; Wajid Ali; Muhammad Irfan (Systems Microbiology and Biomanufacturing, 2024)

Toxic effects of heavy metals on crustaceans and associated health risks in humans: a review - Waqas Waqas; Ye Yuan; Sardar Ali; Mengqian Zhang; Muhammad Shafiq; Wajid Ali; Yongyi Chen; Zifei Xiang; Ruixiang Chen; Mhd Ikhwanuddin; Hongyu Ma (Environmental Chemistry Letters, 2024)

Agriculture and environmental management through nanotechnology: Eco-friendly nanomaterial synthesis for soil-plant systems, food safety, and sustainability - Abdul Wahab; Murad Muhammad; Shahid Ullah; Gholamreza Abdi; Ghulam Mujtaba Shah; Wajid Zaman; Asma Ayaz (Science of The Total Environment, 2024)

Assessing the health risks of heavy metals and seasonal minerals fluctuations in Camellia sinensis cultivars during their growth seasons - Fawad Zaman; Wajid Ali Khattak; Muhammad Ihtisham; Muhammad Ilyas; Ahmad Ali; Abbas Ali; Haroon Khan; Khalid Ali Khan; Dejiang Ni; Hua Zhao; Fu-Sheng Chen (Food and Chemical Toxicology, 2024)

Evaluation of irrigation, drinking, and risk indices for water quality parameters of alpine lakes - Rizwan Ullah; Said Muhammad; Wajid Ali; Sehrish Amin; Sardar Khan; Atta Rasool; Abd El-Latif Hesham; Muhammad Umar; Shaukat Ali; Shahid Iqbal; Ashfaq Ahmad (Environmental Geochemistry and Health, 2024)

Mesozoic structural evolution of the Northern South China Sea margin using potential field modelling - Syed Wajid Hanif Bukhari; Sanzhong Li; Jie Liu; Ze Liu; Muhammad Farhan; Ishaq Kakar (Tectonophysics, 2024)

Spatial distribution and potential health risk assessment for fluoride and nitrate via water consumption in Pakistan - Imran Ud Din; Wajid Ali; Said Muhammad; Mohammed Rafi Shaik; Baji Shaik; Inayat ur Rehman; Cem Tokatli (Journal of Geochemical Exploration, 2024)

Retraction Note: Trends of electronic waste pollution and its impact on the global environment and ecosystem - Rida Akram; Natasha; Shah Fahad; Muhammad Zaffar Hashmi; Abdul Wahid; Muhammad Adnan; Muhammad Mubeen; Naeem Khan; Muhammad Ishaq Asif Rehmani; Muhammadd Awais; Mazhar Abbas; Khurram Shahzad; et al. (Environmental Science and Pollution Research, 2024)

Harnessing the power of bacterial laccases for xenobiotic degradation in water: A 10-year overview - Mujeeb ur Rahman; Muhammad Wajid Ullah; Junaid Ali Shah; Sivasamy Sethupathy; Hazart Bilal; Sidikov Akmal Abdikakharovich; Afaq Ullah Khan; Khalid Ali Khan; Noureddine Elboughdiri; Daochen Zhu (Science of The Total Environment, 2024)

Sustainable production of bacterial flocculants by nylon-6,6 microplastics hydrolysate utilizing Brucella intermedia ZL-06 - Haijuan Zhao; Su Sun; Yongming Cui; Muhammad Wajid Ullah; Khulood Fahad Alabbosh; Noureddine Elboughdiri; Jiangang Zhou (Journal of Hazardous Materials, 2024)

Expression of BSN314 lysozyme genes in Escherichia coli BL21: a study to demonstrate microbicidal and disintegarting potential of the cloned lysozyme - Muhammad Naveed; Sai Wen; Malik Wajid Hussain Chan; Fenghuan Wang; Sadar Aslam; Xian Yin; Baocai Xu; Asad Ullah (Brazilian Journal of Microbiology, 2024)

Assessment of future prediction of urban growth and climate change in district Multan, Pakistan using CA-Markov method - Sajjad Hussain; Muhammad Mubeen; Wajid Nasim; Faisal Mumtaz; Hazem Ghassan Abdo; Raoof Mostafazadeh; Shah Fahad (Urban Climate, 2024)

Heavy metal(loid)s contamination and ecotoxicological hazards in coal, dust, and soil adjacent to coal mining operations, Northwest Pakistan - Imran Ud Din; Said Muhammad; Shah Faisal; Inayat ur Rehman; Wajid Ali (Journal of Geochemical Exploration, 2024)

Compositional data analysis of heavy metal contamination and eco-environmental risks in Himalayan agricultural soils, northern Pakistan - Wajid Ali; Said Muhammad (Journal of Geochemical Exploration, 2023)

A decline in snow cover area of Passu and Ghulkin valleys between 1995 and 2022 - Imran Hussain; Mumtaz Ali; Sher Muhammad; Wajid Hassan; Salar Ali; Zakir Hussain; Syed Hammad Ali; Shaukat Ali; Muhammad Younis Khan (Journal of Mountain Science, 2023)

Petrophysical properties evaluation and reservoir characterization of a giant gas field: Bangladesh case study - Mehedi Hasan; Bineta Mondol; Litao Chen; Muhammad Wajid Manzoor (Arabian Journal of Geosciences, 2023)

LC-ESI-MS analysis, antioxidant, anti-diabetic and molecular docking studies on Corchorus depressus (L.) C.Chr - Shazia Anjum; Humna Tahir; Sadia Sarwar; Wajid Raza; Irum Latif; Hafiz Muhammad Farhan Rasheed; Qaiser Jabeen; Wardah Shahid; Muhammad Ashraf; Syeda Sadaf Zehra; Zaheer Ul-Haq; Muhammad Ayaz; et al. (Natural Product Research, 2023)

Annual effective dose estimation of radon in drinking water sources of Nizampur basin, North Western Pakistan - Jehangir Ijaz; Wajid Ali; Said Muhammad; Hayat Ullah; Danish Ather; Imran Ud Din (Isotopes in Environmental and Health Studies, 2023)

Methyl jasmonate and iron oxide nanoparticles act as elicitors to stimulate production of bioactive antioxidants and metabolites in the in vitro callus cultures of Bergenia ciliata (haw.) Sternb - Tauqeer Sardar; Muhammad Ishtiaq; Muhammad Waqas Mazhar; Mehwish Maqbool; Ihab Mohamed Moussa; Wajid Zaman; Eman A. Mahmoud (South African Journal of Botany, 2023)

Comprehensive evaluation of hydro-chemical processes, suitability, health risks, and sources of groundwater contamination using compositional data analysis, Nizampur basin, Pakistan - Assad Ullah; Wajid Ali; Said Muhammad; Jehangir Ijaz; Faseeha Amir; Shahid Iqbal (Groundwater for Sustainable Development, 2023)

Variations of b-value and the ω-upper bound magnitude of GIII distribution of the Pamir–Hindu Kush region - Khaista Rehman; Wajid Ali; Muhammad Shafique; Aamir Ali; Adnan Barkat; Waqas Ahmed; Muhammad Waqar Azeem (Arabian Journal of Geosciences, 2023)

Pressmud and Farmyard Manure Improve Growth and Yield of Wheat Irrigated with Textile Dye-Contaminated Wastewater through Increasing Nutrient Uptake and Dye Degradation - Muhammad Imran; Muhammad Ashraf; Abdul Rasul Awan; Wajid Ishaque; Hadeeqa Arshad (Journal of Soil Science and Plant Nutrition, 2023)

Bio-fortification of Two Wheat Cultivars with Iron and Zinc Through Their Soil and Foliar Application in Salt-Factored Soil: Growth, Ionic, Physiological, and Biochemical Modifications - Tayyaba Naz; Muhammad Mazhar Iqbal; Shah Fahad; Javaid Akhtar; Muhammad Saqib; Saud Alamri; Manzer H. Siddiqui; Shah Saud; Jabar Zaman Khan Khattak; Shamsher Ali; Shah Hassan; Taufiq Nawaz; et al. (Journal of Plant Growth Regulation, 2023)

Sustainable production of flocculant-containing bacterial cellulose composite for removal of PET nano-plastics - Hong Lu; Su Sun; Jidan Sun; Xiongyi Peng; Ning Li; Muhammad Wajid Ullah; Yanbo Zhang; Li Chen; Jiangang Zhou (Chemical Engineering Journal, 2023)

Fabrication of bio-inspired anisotropic structures from biopolymers for biomedical applications: A review - Xuechu Lu; Haixin Jiao; Yifei Shi; Yan Li; Hongxing Zhang; Yinyi Fu; Jiaqi Guo; Qianqian Wang; Xiang Liu; Mengbo Zhou; Muhammad Wajid Ullah; Jianzhong Sun; et al. (Carbohydrate Polymers, 2023)

Spatial distribution, eco-environmental risks, and source characterization of heavy metals using compositional data analysis in riverine sediments of a Himalayan river, Northern Pakistan - Wajid Ali; Said Muhammad (Journal of Soils and Sediments, 2023)

Fluid source and physicochemical conditions of the polymetallic mineralization in Gawuch Formation, Kohistan Island Arc, NW Pakistan - Muhammad Farhan; Mohammad Arif; Ying Ye; Chun-Feng Li; Xuegang Chen; Dieter Garbe-Schönberg; Tao Wu; Zaheen Ullah; Zahid Hussain; Tehseen Zafar; Izhar Sadiq; Syed Wajid Hanif Bukhari; et al. (Geochemistry, 2023)

Impact of background colorations on growth, movement behavior, and some body physiological factors of Nile tilapia, Oreochromis niloticus - Ahmad Waheed; Hina Naz; Muhammad Wajid; Muhammad Saleem Khan (Fish Physiology and Biochemistry, 2023)

Crop nitrogen (N) utilization mechanism and strategies to improve N use efficiency - Wajid Mahboob; Guozheng Yang; Muhammad Irfan (Acta Physiologiae Plantarum, 2023)

Mediation of gaseous emissions and improving plant productivity by DCD and DMPP nitrification inhibitors: Meta-analysis of last three decades - Muhammad Aammar Tufail; Muhammad Irfan; Wajid Umar; Abdul Wakeel; Ruth A. Schmitz (Environmental Science and Pollution Research, 2023)
Nitrification inhibitors (NIs), especially dicyandiamide (DCD) and 3,4-dimethylpyrazole phosphate (DMPP), have been extensively investigated to mitigate nitrogen (N) losses from the soil and thus improve crop productivity by enhancing N use efficiency. However, to provide crop and soil-specific guidelines about using these NIs, a quantitative assessment of their efficacy in mitigating gaseous emissions, worth for nitrate leaching, and improving crop productivity under different crops and soils is yet required. Therefore, based upon 146 peer-reviewed research studies, we conducted a meta-analysis to quantify the effect of DCD and DMPP on gaseous emissions, nitrate leaching, soil inorganic N, and crop productivity under different variates. The efficacy of the NIs in reducing the emissions of CO 2 , CH 4 , NO, and N 2 O highly depends on the crop, soil, and experiment types. The comparative efficacy of DCD in reducing N 2 O emission was higher than the DMPP under maize, grasses, and fallow soils in both organic and chemical fertilizer amended soils. The use of DCD was linked to increased NH 3 emission in vegetables, rice, and grasses. Depending upon the crop, soil, and fertilizer type, both the NIs decreased nitrate leaching from soils; however, DMPP was more effective. Nevertheless, the effect of DCD on crop productivity indicators, including N uptake, N use efficiency, and biomass/yield was higher than DMPP due to certain factors. Moreover, among soils, crops, and fertilizer types, the response by plant productivity indicators to the application of NIs ranged between 35 and 43%. Overall, the finding of this meta-analysis strongly suggests the use of DCD and DMPP while considering the crop, fertilizer, and soil types. Graphical Abstract

Impacts of COVID-19 pandemic on environment, society, and food security - Hafiz Mohkum Hammad; Hafiz Muhammad Fasihuddin Nauman; Farhat Abbas; Rashid Jawad; Wajid Farhad; Muhammad Shahid; Hafiz Faiq Bakhat; Aitazaz A. Farooque; Muhammad Mubeen; Shah Fahad; Artemi Cerda (Environmental Science and Pollution Research, 2023)

The versatility of nanocellulose, modification strategies, and its current progress in wastewater treatment and environmental remediation - Ajmal Shahzad; Muhammad Wajid Ullah; Jawad Ali; Kazim Aziz; Muhammad Asif Javed; Zhijun Shi; Sehrish Manan; Mazhar Ul-Islam; Mudasir Nazar; Guang Yang (Science of The Total Environment, 2023)

Spatial and temporal analyses of land use changes with special focus on seasonal variation in snow cover in District Chitral; a Hindu Kush mountain region of Pakistan - Muhammad Qasim; Mudassir Khan; Wajid Rashid (Remote Sensing Applications: Society and Environment, 2023)

MoS4-LDH: A dual centre Fe-based layered double hydroxide catalyst for efficient atrazine removal and peroxymonsulfate activation - Jawad Ali; Dan Li; Ajmal Shahzad; Muhammad Wajid Ullah; Jerosha Ifthikar; Muhammed Asif; Chen Yanan; Xie Lei; Zhuqi Chen; Songlin Wang (Chemical Engineering Journal, 2023)

Polyethylene terephthalate hydrolysate increased bacterial cellulose production - Jiangang Zhou; Jidan Sun; Mati Ullah; Quan Wang; Yanbo Zhang; Gang Cao; Li Chen; Muhammad Wajid Ullah; Su Sun (Carbohydrate Polymers, 2023)

Heavy metal(loid)s contamination and potential risk assessment via groundwater consumption in the district of Hangu, Pakistan - Imran Ud Din; Said Muhammad; Shah Faisal; Inayat ur Rehman; Wajid Ali (Environmental Science and Pollution Research, 2022)

Maintenance of Tissue Water Status, Osmoregulation, and Antioxidant Defence System Improves Heat Tolerance in Okra Genotypes with Contrast Heat Tolerance - Muhammad Wajid Khan; Zahoor Hussain; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2022)

An integrated approach towards marble waste management: GIS, SFA, and recycling options - Muhammad Fawad; Farid Ullah; Wisal Shah; Muhammad Jawad; Kifayatullah Khan; Wajid Rashid (Environmental Science and Pollution Research, 2022)

Potentially Harmful Elements Accumulation and Health Risk Assessment of Edible Fish Tissues Caught from the Phander Valley, Northern Pakistan - Said Muhammad; Wajid Ali; Inayat ur Rehman (Biological Trace Element Research, 2022)

Catalytic potential of endophytes facilitates synthesis of biometallic zinc oxide nanoparticles for agricultural application - Saddam Saqib; Amna Nazeer; Muhammad Ali; Wajid Zaman; Muhammad Younas; Asim Shahzad; Sunera; Momina Nisar (BioMetals, 2022)

Immunological characterization of chitosan adjuvanted outer membrane proteins of Salmonella enterica serovar Typhi as multi-epitope typhoid vaccine candidate - Ambreen Ayub; Muhammad Usman; Ayesha Ihsan; Quratul Ain; Asad Bashir Awan; Muhammad Wajid; Aamir Ali; Abdul Haque; Mazhar Iqbal; Yasra Sarwar (Molecular Biology Reports, 2022)

Assessment of land use/land cover changes and its effect on land surface temperature using remote sensing techniques in Southern Punjab, Pakistan - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Hamid Majeed; Saeed Ahmad Qaisrani; Hafiz Mohkum Hammad; Muhammad Amjad; Iftikhar Ahmad; Shah Fahad; Naveed Ahmad; Wajid Nasim (Environmental Science and Pollution Research, 2022)

Circadian Variation in Activities of Blackbuck Under Captivity in Punjab, Pakistan - Zahid Farooq; Muhammad Iqbal; Muhammad Saleem Khan; Sana Asad; Muhammad Wajid (Proceedings of the Zoological Society, 2022)

Exploring the potential effect of Achnatherum splendens L.–derived biochar treated with phosphoric acid on bioavailability of cadmium and wheat growth in contaminated soil - Muhammad Irfan; Khadim Dawar; Shah Fahad; Imran Mehmood; Saud Alamri; Manzer H. Siddiqui; Shah Saud; Jabar Zaman Khan Khattak; Shamsher Ali; Shah Hassan; Taufiq Nawaz; Hafiz Mohkum Hammad; et al. (Environmental Science and Pollution Research, 2022)

Correction to: Molecular detection of Cryptosporidium: an emerging parasite in different water sources of 2010 flood‑affected district Nowshera, Pakistan - Shaukat Ali Khan; Imran Khan; Izaz Ali; Amir Muhammad Khan; Muhammad Anees; Khurshaid Ali Khan; Wajid Rashid; Noorul Akbar (Archives of Microbiology, 2022)

Design, synthesis, in vitro evaluation, and docking studies on ibuprofen derived 1,3,4-oxadiazole derivatives as dual α-glucosidase and urease inhibitors - Saima Daud; Obaid-ur-Rahman Abid; Asma Sardar; Basit Ali Shah; Muhammad Rafiq; Abdul Wadood; Mehreen Ghufran; Wajid Rehman; Zain-ul-Wahab; Fatima Iftikhar; Rifhat Sultana; Habiba Daud; et al. (Medicinal Chemistry Research, 2022)

Correction to: Bioaccumulation of lead in different varieties of wheat plant irrigated with wastewater in remote agricultural regions - Wuyi Liu; Asma Zafar; Zafar Iqbal Khan; Muhammad Nadeem; Kafeel Ahmad; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq (Environmental Science and Pollution Research, 2022)

Review of hospital plastic waste management strategies for Pakistan - Yasir Qayyum Gill; Mudasar Khurshid; Umer Abid; Muhammad Wajid Ijaz (Environmental Science and Pollution Research, 2022)

Synthesis and evaluation of Ca-doped ferrihydrite as a novel adsorbent for the efficient removal of fluoride - Khalil Ahmad; Izaz Ali Shah; Sharafat Ali; Muhammad Tariq Khan; Muhammad Bilal Ahmed Qureshi; Syed Hassan Ali Shah; Asmat Ali; Wajid Rashid; Hifza Nayab Gul (Environmental Science and Pollution Research, 2022)

Hydrogen Sulfide: A Novel Gaseous Molecule for Plant Adaptation to Stress - Mukhtar Ahmed; Shah Fahad; Muhammad Arif Ali; Sajjad Hussain; Muhammad Tariq; Fariha Ilyas; Shakeel Ahmad; Shah Saud; Hafiz Mohkum Hammad; Wajid Nasim; Chao Wu; Hongyan Liu (Journal of Plant Growth Regulation, 2021)

Using space–time scan statistic for studying the effects of COVID-19 in Punjab, Pakistan: a guideline for policy measures in regional agriculture - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Shah Fahad; Wajid Nasim; Hafiz Mohkum Hammad; Ghulam Mustafa Shah; Behzad Murtaza; Muhammad Tahir; Saima Parveen (Environmental Science and Pollution Research, 2021)

Homozygosity mapping coupled with whole-exome sequencing and protein modelling identified a novel missense mutation in GUCY2D in a consanguineous Pakistani family with Leber congenital amaurosis - HADIA GUL; ABDUL HALEEM SHAH; RICARDO HARRIPAUL; SUMRA WAJID ABBASI; MUHAMMAD FAHEEM; MUHAMMAD ZUBAIR; MUHAMMAD MUZAMMAL; SAADULLAH KHAN; JOHN B. VINCENT; MUZAMMIL AHMAD KHAN (Journal of Genetics, 2021)

Correction to: Lineament mapping for a part of the central Sulaiman fold–Thrust Belt (SFTB), Pakistan - Ali Abbas Wajid; Muhammad Anees; Shams ul Alam; Jodat Kamran Gorchani; Khurram Shahzad; Asif Israr; Muhammad Shafique (Arabian Journal of Geosciences, 2021)

Molecular detection of Cryptosporidium: an emerging parasite in different water sources of 2010 flood-affected district Nowshera, Pakistan - Shaukat Ali Khan; Imran Khan; Izaz Ali; Amir Muhammad Khan; Muhammad Anees; Khurshaid Ali Khan; Wajid Rashid; Noorul Akbar (Archives of Microbiology, 2021)

Appraisal of iron accumulation in soil, forages, and blood plasma of sheep and goats: a case study in different districts of Punjab, Pakistan - Zafar Iqbal Khan; Kafeel Ahmad; Samra Siddique; Kinza Wajid; Humayun Bashir; Muhammad Nadeem; Muhammad Fiaz Qamar; Muhammad Fahad Ullah; Saif Ur Rehman (Environmental Science and Pollution Research, 2021)

A comparison of hepatotoxicity induced by different lengths of tungsten trioxide nanorods and the protective effects of melatonin in BALB/c mice - Lin Mao; Lifang Zheng; Huihui You; Muhammad Wajid Ullah; Haoyan Cheng; Qing Guo; Zhihong Zhu; Zhuge Xi; Rui Li (Environmental Science and Pollution Research, 2021)

Optimizing different adaptive strategies by using crop growth modeling under IPCC climate change scenarios for sustainable wheat production - Muhammad Rizwan Shahid; Abdul Wakeel; Wajid Ishaque; Samia Ali; Kamran Baksh Soomro; Muhammad Awais (Environment, Development and Sustainability, 2021)

Lineament mapping for a part of the Central Sulaiman Fold–Thrust Belt (SFTB), Pakistan - Ali Abbas Wajid; Muhammad Anees; Shams ul Alam; Jodat Kamran Gorchani; Khurram Shahzad; Asif Israr; Muhammad Shafique (Arabian Journal of Geosciences, 2021)
This study aims to analyze the lineaments using the field data and a remote sensing approach, to describe their relationship with the folds, faults, and regional tectonic stress of the central Sulaiman Fold-Thrust Belt. Joint data, from nine anticlines, has been collected using the scanline method and classified into three sets (JS1, JS2, and JS3) based on their geometrical relationships. Lineaments extracted from the 30 m digital elevation model have been classified subsequently into three lineament sets (LS1, LS2, and LS3) based on the azimuths from the corresponding joint sets. A very high correlation coefficient (rs = 0.97), between the azimuths of the field joints and the remotely sensed lineaments, has been observed which validates that the lineaments are the regional representation of the local field joints. The geometrical relationship of the lineament sets with the fold hinges indicates that the older LS1 and LS2 are strongly related to the regional folding episode, while the younger LS3 is a result of local shears. The chronological interpretation of the deformational events responsible for the lineament sets is constrained by the presence of the Kingri Fault, which induces a strike-slip component within the study area. Furthermore, the controls on the joint and lineament sets, established using multivariate statistics to decipher the effects of lithological and structural contrasts on the lineament density, reveal that an increase in the lineament density can be attributed to the competence and thickness of the rock units as well as the variable local stresses across the different folds. Based on the orientations of these lineament sets, the cumulative direction of the compressive event in the NW-SE direction (310–320) coincides with the regional stress direction of the SFTB.

RETRACTED ARTICLE: Evaluation of toxicity potential of cobalt in wheat irrigated with wastewater: health risk implications for public - Fu Chen; Zafar Iqbal Khan; Asma Zafar; Jing Ma; Muhammad Nadeem; Kafeel Ahmad; Shehzadi Mahpara; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; et al. (Environmental Science and Pollution Research, 2021)

Influence of semi-arid environment on radiation use efficiency and other growth attributes of lentil crop - Muhammad Habib ur Rahman; Ishfaq Ahmad; Depeng Wang; Shah Fahad; Muhammad Afzal; Abdul Ghaffar; Qaisar Saddique; Mehmood Alam Khan; Shah Saud; Shah Hassan; Muhammad Fahad; Mairaj Din; et al. (Environmental Science and Pollution Research, 2021)

Appraisal of chromium in chicken reared on maize irrigated with sewage water - Zill-e-Huma; Zafar Iqbal Khan; Ijaz Rasool Noorka; Kafeel Ahmad; Kinza Wajid; Muhammad Nadeem; Mudasra Munir; Ifra Saleem Malik; Madiha Kiran; Tahir Hussain; Muhammad F. Qamar; Tasneem Ahmad; et al. (Environmental Science and Pollution Research, 2021)

Pattern of Trace Metal Uptake in Pearl Millet as a Result of Application of Organic and Synthetic Fertilizers - Kinza Wajid; Kafeel Ahmad; Zafar Iqbal Khan; Muhammad Nadeem (International Journal of Environmental Research, 2021)

Future climatic changes, extreme events, related uncertainties, and policy recommendations in the Hindu Kush sub-regions of Pakistan - Shaukat Ali; Alia Saeed; Rida Sehar Kiani; Sher Muhammad; Firdos Khan; Romaisa Babar; Asif Khan; Muhammad Shahid Iqbal; Muhammad Arif Goheer; Wajid Naseem; Shah Fahad (Theoretical and Applied Climatology, 2021)

Synthesis, urease inhibition screening and molecular docking studies of piperonal based imine derivatives - Obaid-ur-Rahman Abid; Saima Daud; Asma Sardar; Wajid Rehman; Abdul Wadood; Ashfaq Ur Rehman; Toheed Akhter; Iram Bibi; Zaheer Ahmad; Muhammad Yasir (Medicinal Chemistry Research, 2021)

Correction to: Appraisal of chromium in chicken reared on maize irrigated with sewage water - Zill-e-Huma; Zafar Iqbal Khan; Ijaz Rasool Noorka; Kafeel Ahmad; Kinza Wajid; Muhammad Nadeem; Mudasra Munir; Ifra Saleem Malik; Madiha Kiran; Tahir Hussain; Muhammad F. Qamar; Tasneem Ahmad; et al. (Environmental Science and Pollution Research, 2021)

Bioaccumulation of cadmium in different genotypes of wheat crops irrigated with different sources of water in agricultural regions - Asma Zafar; Zafar Iqbal Khan; Wuyi Liu; Humayun Bashir; Kafeel Ahmad; Kinza Wajid; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; Muhammad Nadeem; Tasneem Ahmad; Ijaz Rasool Noorka; et al. (Environmental Science and Pollution Research, 2021)

Evaluation of rapid polymyxin Nordmann Poirel test for detection of polymyxin resistance in clinical isolates of Enterobacteriaceae - Muhammad Shoaib; Ashfaq Hussain; Luqman Satti; Wajid Hussain; Gohar Zaman; Faisal Hanif (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Correction to: A study on the transfer of chromium from meadows to grazing livestock: an assessment of health risk - Zafar Iqbal Khan; Kafeel Ahmad; Samra Siddique; Tasneem Ahmad; Humayun Bashir; Mudasra Munir; Shahzadi Mahpara; Ifra Saleem Malik; Kinza Wajid; Ilker Ugulu; Muhammad Nadeem; Ijaz Rasool Noorka; et al. (Environmental Science and Pollution Research, 2020)

Developing the first halophytic turfgrasses for the urban landscape from native Arabian desert grass - Muhammad Zamin; Shah Fahad; Abdul Mateen Khattak; Muhammad Adnan; Fazli Wahid; Ahmad Raza; Depeng Wang; Shah Saud; Muhammad Noor; Hafiz Faiq Bakhat; Muhammad Mubeen; Hafiz Mohkum Hammad; et al. (Environmental Science and Pollution Research, 2020)

Using GIS tools to detect the land use/land cover changes during forty years in Lodhran District of Pakistan - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Waseem Akram; Hafiz Mohkum Hammad; Mazhar Ali; Nasir Masood; Asad Amin; Hafiz Umar Farid; Syeda Refat Sultana; Shah Fahad; Depeng Wang; et al. (Environmental Science and Pollution Research, 2020)

Bioaccumulation of lead in different varieties of wheat plant irrigated with wastewater in remote agricultural regions - Wuyi Liu; Asma Zafar; Zafar Iqbal Khan; Muhammad Nadeem; Kafeel Ahmad; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq (Environmental Science and Pollution Research, 2020)

A study on the transfer of chromium from meadows to grazing livestock: an assessment of health risk - Zafar Iqbal Khan; Kafeel Ahmad; Samra Siddique; Tasneem Ahmad; Humayun Bashir; Mudasra Munir; Shahzadi Mahpara; Ifra Saleem Malik; Kinza Wajid; Ilker Ugulu; Muhammad Nadeem; Ijaz Rasool Noorka; et al. (Environmental Science and Pollution Research, 2020)

Arsenic distribution and metabolism genes abundance in Paddy soils from Punjab and Sindh provinces, Pakistan - Muhammad Zaffar Hashmi; Aatika Kanwal; Siwatt Pongpiachan; Xiaomei Su; Wajid Nasim; Mumtaz Ali Saand; Muhammad Mubeen; Rida Akram; Shuhong Wang; Zulkfil Ahmed (Arabian Journal of Geosciences, 2020)

Extracting mass concentration time series features for classification of indoor and outdoor atmospheric particulates - Lal Hussain; Wajid Aziz; Sharjil Saeed; Muhammad Rafique; Malik Sajjad Ahmed Nadeem; Seong-O Shim; Sania Aftar; Jawad-ur-Rehman Pirzada (Acta Geophysica, 2020)

Effect of Organic Manure and Mineral Fertilizers on Bioaccumulation and Translocation of Trace Metals in Maize - Kinza Wajid; Kafeel Ahmad; Zafar Iqbal Khan; Muhammad Nadeem; Humayun Bashir; Fu Chen; Ilker Ugulu (Bulletin of Environmental Contamination and Toxicology, 2020)

The role of garlic oil in the amelioration of oxidative stress and tissue damage in rohu Labeo rohita treated with silver nanoparticles - Muhammad Saleem Khan; Naureen Aziz Qureshi; Farhat Jabeen; Muhammad Wajid; Sabeen Sabri; Muhammad Shakir (Fisheries Science, 2020)

Isolation and genetic characterization of virulent strains of avian paramyxovirus-1 from multiple avian species in Azad Jammu and Kashmir 2017–2018 - Abid Hussain; Abdul Wajid; Safa Ather; Kashaf Alyas; Muhammad Awais; Muhammad Rizwan Khan; Tanveer Hussain; Masroor Ellahi Babar (Brazilian Journal of Microbiology, 2020)

The potential applications of picotechnology in biomedical and environmental sciences - Muhammad Zeeshan Qasim; Hafiz Mohkum Hammad; Farhat Abbas; Shafqat Saeed; Hafiz Faiq Bakhat; Wajid Nasim; Wajid Farhad; Faiz Rabbani; Shah Fahad (Environmental Science and Pollution Research, 2020)

Study of land cover/land use changes using RS and GIS: a case study of Multan district, Pakistan - Sajjad Hussain; Muhammad Mubeen; Waseem Akram; Ashfaq Ahmad; Muhammad Habib-ur-Rahman; Abdul Ghaffar; Asad Amin; Muhammad Awais; Hafiz Umar Farid; Amjad Farooq; Wajid Nasim (Environmental Monitoring and Assessment, 2020)

Assessment of arsenic exposure by drinking well water and associated carcinogenic risk in peri-urban areas of Vehari, Pakistan - Ali Haidar Shah; Muhammad Shahid; Sana Khalid; Natasha; Zunaira Shabbir; Hafiz Faiq Bakhat; Behzad Murtaza; Amjad Farooq; Muhammad Akram; Ghulam Mustafa Shah; Wajid Nasim; Nabeel Khan Niazi (Environmental Geochemistry and Health, 2020)

Future water demand modeling using water evaluation and planning: a case study of the Indus Basin in Pakistan - Daniyal Hassan; Muhammad Naseer Rais; Waqas Ahmed; Rakhshinda Bano; Steven J. Burian; Muhammad Wajid Ijaz; Faris Ahmed Bhatti (Sustainable Water Resources Management, 2019)

Socio-political and ecological stresses on traditional pastoral systems: A review - Khurshid Muhammad; Nafees Mohammad; Khan Abdullah; Somuncu Mehmet; Ahmad Khan Ashfaq; Rashid Wajid (Journal of Geographical Sciences, 2019)

Evaluation of toxic potential of metals in wheat crop grown in wastewater-contaminated soil in Punjab, Pakistan - Zafar Iqbal Khan; Kafeel Ahmad; Fauzia Batool; Kinza Wajid; Naunain Mehmood; Asma Ashfaq; Humayun Bashir; Muhammad Nadeem; Saif Ullah (Environmental Science and Pollution Research, 2019)

Immunoprotective role of LaSota vaccine under immunosuppressive conditions in chicken challenged with velogenic avian avulavirus-1 - Iqra Rauf; Abdul Wajid; Irshad Hussain; Safa Ather; Muhammad Asad Ali (Tropical Animal Health and Production, 2019)

Adsorption mechanism of Pb2+ ions by Fe3O4, SnO2, and TiO2 nanoparticles - Mahfooz-ur Rehman; Wajid Rehman; Muhammad Waseem; Shahzad Hussain; Sirajul Haq; Muhammad Anees-ur Rehman (Environmental Science and Pollution Research, 2019)

Residues of endosulfan in cotton growing area of Vehari, Pakistan: an assessment of knowledge and awareness of pesticide use and health risks - Ashfaq Ahmad; Muhammad Shahid; Sana Khalid; Habiba Zaffar; Tatheer Naqvi; Arshid Pervez; Muhammad Bilal; Muhammad Arif Ali; Ghulam Abbas; Wajid Nasim (Environmental Science and Pollution Research, 2019)

Quantification of spatial temporal variability of snow cover and hydro-climatic variables based on multi-source remote sensing data in the Swat watershed, Hindukush Mountains, Pakistan - Muhammad Naveed Anjum; Yongjian Ding; Donghui Shangguan; Junguo Liu; Ijaz Ahmad; Muhammad Wajid Ijaz; Muhammad Imran Khan (Meteorology and Atmospheric Physics, 2019)

RETRACTED ARTICLE: Trends of electronic waste pollution and its impact on the global environment and ecosystem - Rida Akram; Natasha; Shah Fahad; Muhammad Zaffar Hashmi; Abdul Wahid; Muhammad Adnan; Muhammad Mubeen; Naeem Khan; Muhammad Ishaq Asif Rehmani; Muhammadd Awais; Mazhar Abbas; Khurram Shahzad; et al. (Environmental Science and Pollution Research, 2019)

Evaluation of Potential Toxic Metals Accumulation in Wheat Irrigated with Wastewater - Kafeel Ahmad; Kinza Wajid; Zafar Iqbal Khan; Ilker Ugulu; Hafsa Memoona; Madiha Sana; Khalid Nawaz; Ifra Saleem Malik; Humayun Bashir; Muhammad Sher (Bulletin of Environmental Contamination and Toxicology, 2019)

Toxicological potential of cobalt in forage for ruminants grown in polluted soil: a health risk assessment from trace metal pollution for livestock - Zafar Iqbal Khan; Nimra Arshad; Kafeel Ahmad; Muhammad Nadeem; Asma Ashfaq; Kinza Wajid; Humayun Bashir; Mudasra Munir; Bushra Huma; Hafsa Memoona; Madiha Sana; Khalid Nawaz; et al. (Environmental Science and Pollution Research, 2019)

Composting of municipal solid waste by different methods improved the growth of vegetables and reduced the health risks of cadmium and lead - Ghulam Mustafa Shah; Nadia Tufail; Hafiz Faiq Bakhat; Iftikhar Ahmad; Muhammad Shahid; Hafiz Mohkum Hammad; Wajid Nasim; Atika Waqar; Muhammad Rizwan; Renjie Dong (Environmental Science and Pollution Research, 2019)

Optimizing irrigation and nitrogen requirements for maize through empirical modeling in semi-arid environment - Ishfaq Ahmad; Syed Aftab Wajid; Ashfaq Ahmad; Muhammad Jehanzeb Masud Cheema; Jasmeet Judge (Environmental Science and Pollution Research, 2019)

Interaction between PGPR and PGR for water conservation and plant growth attributes under drought condition - Naeem Khan; Asghari Bano; Muhammad Adnan Shahid; Wajid Nasim; MD Ali Babar (Biologia, 2018)

Effect of foliar-applied iron complexed with lysine on growth and cadmium (Cd) uptake in rice under Cd stress - Arooj Bashir; Muhammad Rizwan; Shafaqat Ali; Muhammad Zia ur Rehman; Wajid Ishaque; Muhammad Atif Riaz; Arosha Maqbool (Environmental Science and Pollution Research, 2018)

Influence of composted poultry manure and irrigation regimes on some morpho-physiology parameters of maize under semiarid environments - Wajid Farhad; Mumtaz Akhtar Cheema; Hafiz Mohkum Hammad; Muhammad Farrukh Saleem; Shah Fahad; Farhat Abbas; Ikramullah Khosa; Hafiz Faiq Bakhat (Environmental Science and Pollution Research, 2018)

Using Growth and Ionic Contents of Wheat Seedlings as Rapid Screening Tool for Salt Tolerance - Wajid Mahboob; Muhammad Athar Khan; Muhammad Ubaidullah Shirazi; Saba Mumtaz; Aisha Shereen (Journal of Crop Science and Biotechnology, 2018)

Potential impacts of climate change and adaptation strategies for sunflower in Pakistan - Muhammad Awais; Aftab Wajid; Muhammad Farrukh Saleem; Wajid Nasim; Ashfaq Ahmad; Muhammad Aown Sammar Raza; Muhammad Usman Bashir; Muhammad Mubeen; Hafiz Mohkum Hammad; Muhammad Habib ur Rahman; Umer Saeed; Muhammad Naveed Arshad; et al. (Environmental Science and Pollution Research, 2018)

Management of tannery wastewater for improving growth attributes and reducing chromium uptake in spinach through citric acid application - Arosha Maqbool; Shafaqat Ali; Muhammad Rizwan; Wajid Ishaque; Nasir Rasool; Muhammad Zia ur Rehman; Arooj Bashir; Muhammad Abid; Longhua Wu (Environmental Science and Pollution Research, 2018)

Physiological responses of wheat to drought stress and its mitigation approaches - Zahoor Ahmad; Ejaz Ahmad Waraich; Sajjad Akhtar; Shazia Anjum; Tanveer Ahmad; Wajid Mahboob; Osama Bin Abdul Hafeez; Terence Tapera; Maryke Labuschagne; Muhammad Rizwan (Acta Physiologiae Plantarum, 2018)

Current status and future possibilities of molecular genetics techniques in Brassica napus - Muhammad Afzal; Salem Safer Alghamdi; Muhammad Habib ur Rahman; Awais Ahmad; Tahir Farooq; Mukhtar Alam; Imtiaz Ali Khan; Hidayat Ullah; Wajid Nasim; Shah Fahad (Biotechnology Letters, 2018)

Regional climate assessment of precipitation and temperature in Southern Punjab (Pakistan) using SimCLIM climate model for different temporal scales - Asad Amin; Wajid Nasim; Muhammad Mubeen; Saleem Sarwar; Peter Urich; Ashfaq Ahmad; Aftab Wajid; Tasneem Khaliq; Fahd Rasul; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Hussani Mubarak; et al. (Theoretical and Applied Climatology, 2018)

Radiation efficiency and nitrogen fertilizer impacts on sunflower crop in contrasting environments of Punjab, Pakistan - Wajid Nasim; Ashfaq Ahmad; Asad Amin; Muhammad Tariq; Muhammad Awais; Muhammad Saqib; Khawar Jabran; Ghulam Mustafa Shah; Syeda Refat Sultana; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Muhammad Zaffar Hashmi; et al. (Environmental Science and Pollution Research, 2018)

Foliar application of aspartic acid lowers cadmium uptake and Cd-induced oxidative stress in rice under Cd stress - Muhammad Rizwan; Shafaqat Ali; Muhammad Zaheer Akbar; Muhammad Bilal Shakoor; Abid Mahmood; Wajid Ishaque; Afzal Hussain (Environmental Science and Pollution Research, 2017)

Nitrogen and plant population change radiation capture and utilization capacity of sunflower in semi-arid environment - Muhammad Awais; Aftab Wajid; Muhammad Usman Bashir; Muhammad Habib-ur-Rahman; Muhammad Aown Sammar Raza; Ashfaq Ahmad; Muhammad Farrukh Saleem; Hafiz Mohkum Hammad; Muhammad Mubeen; Umer Saeed; Muhammad Naveed Arshad; Shah Fahad; et al. (Environmental Science and Pollution Research, 2017)

Environment polluting conventional chemical control compared to an environmentally friendly IPM approach for control of diamondback moth, Plutella xylostella (L.), in China: a review - Muhammad Shakeel; Muhammad Farooq; Wajid Nasim; Waseem Akram; Fawad Zafar Ahmad Khan; Waqar Jaleel; Xun Zhu; Haichen Yin; Shuzhong Li; Shah Fahad; Saddam Hussain; Bhagirath Singh Chauhan; et al. (Environmental Science and Pollution Research, 2017)

Water-saving technologies affect the grain characteristics and recovery of fine-grain rice cultivars in semi-arid environment - Khawar Jabran; Muhammad Riaz; Mubshar Hussain; Wajid Nasim; Umar Zaman; Shah Fahad; Bhagirath Singh Chauhan (Environmental Science and Pollution Research, 2017)

Current advancements of magnetic nanoparticles in adsorption and degradation of organic pollutants - Mazhar Ul-Islam; Muhammad Wajid Ullah; Shaukat Khan; Shehrish Manan; Waleed Ahmad Khattak; Wasi Ahmad; Nasrullah Shah; Joong Kon Park (Environmental Science and Pollution Research, 2017)

Agroforestry: a sustainable environmental practice for carbon sequestration under the climate change scenarios—a review - Farhat Abbas; Hafiz Mohkum Hammad; Shah Fahad; Artemi Cerdà; Muhammad Rizwan; Wajid Farhad; Sana Ehsan; Hafiz Faiq Bakhat (Environmental Science and Pollution Research, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Phytomanagement of heavy metals in contaminated soils using sunflower: A review - Muhammad Rizwan; Shafaqat Ali; Hina Rizvi; Jörg Rinklebe; Daniel C. W. Tsang; Erik Meers; Yong Sik Ok; Wajid Ishaque (Critical Reviews in Environmental Science and Technology, 2016)

Economic assessment of different mulches in conventional and water-saving rice production systems - Khawar Jabran; Mubshar Hussain; Shah Fahad; Muhammad Farooq; Ali Ahsan Bajwa; Hesham Alharrby; Wajid Nasim (Environmental Science and Pollution Research, 2016)

Correlation studies on nitrogen for sunflower crop across the agroclimatic variability - Wajid Nasim; Hatem Belhouchette; Muhammad Tariq; Shah Fahad; Hafiz Mohkum Hammad; Muhammad Mubeen; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary; Imran Khan; Faisal Mahmood; Tauqeer Abbas; Fahd Rasul; et al. (Environmental Science and Pollution Research, 2016)

Spatio-temporal variations of b-value in and around north Pakistan - Khaista Rehman; Asghar Ali; Sajjad Ahmed; Wajid Ali; Aamir Ali; Muhammad Younis Khan (Journal of Earth System Science, 2015)

The effect of gestational diabetes on proliferation capacity and viability of human umbilical cord-derived stromal cells - Nadia Wajid; Rashida Naseem; Sanam Saiqa Anwar; Sana Javaid Awan; Muhammad Ali; Sara Javed; Fatima Ali (Cell and Tissue Banking, 2015)

Combining ability through line × tester analysis for phenological, seed yield, and oil traits in sunflower (Helianthus annuus L.) - Shahnaz Memon; Muhammad Jurial Baloch; Gul Muhammad Baloch; Wajid Ali Jatoi (Euphytica, 2015)

Silicon (Si) alleviates cotton (Gossypium hirsutum L.) from zinc (Zn) toxicity stress by limiting Zn uptake and oxidative damage - Shad Ali Anwaar; Shafaqat Ali; Skhawat Ali; Wajid Ishaque; Mujahid Farid; Muhammad Ahsan Farooq; Ullah Najeeb; Farhat Abbas; Muhammad Sharif (Environmental Science and Pollution Research, 2015)

Synthesis, characterization antibacterial and antifungal activity of some transition metal complexes - Wajid Rehman; Zonera Hassan; Umer Rashid; Fazal Rahim; Obaid-Ur-Rahman Abid; Muhammad Waseem (Medicinal Chemistry Research, 2014)

Monitoring of cotton dust and health risk assessment in small-scale weaving industry - Muhammad Wajid Tahir; Muhammad Waseem Mumtaz; Shanza Tauseef; Muqadas Sajjad; Awais Nazeer; Nazish Farheen; Muddsar Iqbal (Environmental Monitoring and Assessment, 2012)

Complexity analysis of stride interval time series by threshold dependent symbolic entropy - Wajid Aziz; Muhammad Arif (European Journal of Applied Physiology, 2006)

A novel autosomal recessive non-syndromic hearing impairment locus (DFNB47) maps to chromosome 2p25.1-p24.3 - Muhammad Jawad Hassan; Regie Lyn P. Santos; Muhammad Arshad Rafiq; Maria H. Chahrour; Thanh L. Pham; Muhammad Wajid; Nadine Hijab; Michael Wambangco; Kwanghyuk Lee; Muhammad Ansar; Kai Yan; Wasim Ahmad; et al. (Human Genetics, 2006)